Molteno Kannaskoppia: Mid-Triassic gymnosperm case study for whole-plant taxonomy - Anderson, John M; Anderson, Heidi M (Evolutionary Studies Institute, 2023)
The flora from the Upper Triassic Molteno Formation, southern Africa, is the most extensively collected and documented macro-flora in the Gondwana Triassic. The collection includes c. 30 000 catalogue slabs from 100 assemblages in 43 super-localities. Some 61 genera and 211 species have been described in a series of publications from the early 1980s covering most of the plant groups. In this volume, the genus Kannaskoppia and affiliates, in the order Petriellales, are described in greater detail than previously in 2003, and offer the opportunity to explore the question of whole-plant genera and species. The ovulate strobilus, Kannaskoppia, with the single species K. vincularis, occurs in only one assemblage – where it is common with c. 50 specimens, including five with both the foliage and strobili found attached to shoots. This find remains unique for the Gondwana Triassic. The male strobilus, Kannaskoppianthus, with eight species recognized (four described as new), occurs in 12 assemblages; at two of these, both distinct species, it is found attached to shoots. The foliage Rochipteris, with 12 Molteno species recognized (seven described as new), is known from 26 of the 100 Molteno assemblages; at four of these, in three distinct species, the foliage has been found attached to shoots. For each of the these 26 assemblages, geographic and stratigraphic information is provided, plus the associated fl ora and plant/insect records. As in previous Molteno publications, the Palaeodeme approach is followed in the circumscription of species. All the Reference Palaeodemes are illustrated by line drawings and extensive photographs as are the more important Sister Palaeodemes. A comprehensive revision of the Gondwana Triassic records of Rochipteris has resulted in 24 accepted species, of which seven occur only in the Molteno Flora. All previously illustrated material is listed in the hypodigm table and used for comparison and nomenclatural considerations with the Molteno specimens. Whole-plant species from the Molteno have been recognized, based on considerations of affiliation and taphonomy. For each of these the habit and habitat are reconstructed in colour. Each is placed in its most-likely habitat within the Molteno Biome, with the seven primary habitats (ecozones) as recognized previously for the Formation. These plants are typically considered perennials to about one metre high that grew in a variety of habitats and were often associated with Dicroidium/Umkomasia or with Heidiphyllum/Telemachus trees. The current study of Kannaskoppia, and affiliates, supports previous phylogenetic, anatomical and ecological studies that amongst the gymnosperms the order Petriellales constitutes a likely sister group of the angiosperms.
Keywords: Stormberg Group; Main Karoo Basin; Land Plants; fossils